Growth of irrigated and fertilized pequi trees in the Cerrado of Goiás, Brazil (2018)
The objective of this study is to evaluate the growth of pequi trees in function of irrigation and organic fertilization. A total of 96 pequi plants (6-8 years of age), spaced 5 x 5 m, were used in a randomized blocks experiment with six plots and for repetitions. Four treatments were evaluated: IF = Irrigation with fertilization, IWF = Irrigation without fertilization, WIF = Without irrigation with fertilization, and WIWF = Without irrigation and without fertilization, in subdivided plots. The irrigation system was microsprinklers. The volume of water applied was estimated by the evapotranspiration of pequi trees. Cover fertilizations were performed in Nov/2014 using composting material and Yorim, and in Nov/2015 using tanned cattle manure and chicken litter. The growth was monthly evaluated by the height and the stem perimeter, and the canopy was evaluated in a 7.1 years old orchard. Leaf temperature and transpiration were evaluated by sap flow in irrigated and non-irrigated trees. The pequi tree did not respond to treatments in terms of height and stem perimeter. Irrigation provided trees with larger canopy areas. When irrigated, the leaf temperature of pequi trees remained below average air temperatures, independently of dry or rainy periods. Without irrigation, plants presented water stress during the dry season. Under rainy conditions, the mean transpiration of the pequi tree was 24.09 L d-1 per plant. When irrigated, it was on average 42.29 L d-1 per plant.